The Development of International Refugee Protection through the Practice of the UN Security Council - Christiane Ahlborn (Graduate Institute Publications, 2010)
This paper examines the ambivalent influence of the UN Security Council's practice on the development of international refugee protection since the early 1990s. While the international refugee protection regime did not originally foresee a role for the Security Council, the increasingly complex security challenges in the post-Cold War era have led to its de facto inclusion in the institutional framework of protection. After having used its wide discretionary powers under the UN Charter to lin...